CEO Ethnicity, Operational Complexity, and Financial Reporting Complexity on Financial Reporting Timeliness: The Moderating Role of Leverage in Indonesian Infrastructure Firms (2021–2024) - Suparman; Dirvi Surya Abbas; Anita Ardiyanti (LPPM UBP, 2026)
This study investigates the effect of CEO ethnicity, operational complexity, and financial reporting complexity on financial reporting timeliness, with leverage serving as a moderating variable in Indonesian infrastructure firms during 2021–2024. Although prior research has examined financial determinants of reporting timeliness, limited attention has been given to executive demographic characteristics, particularly CEO ethnicity, within emerging market contexts. In addition, empirical findings regarding organizational complexity remain inconsistent, and the moderating role of leverage in shaping reporting discipline is underexplored. Grounded in Upper Echelons Theory, Agency Theory, and Signaling Theory, this study employs panel data regression analysis on infrastructure firms listed on the Indonesia Stock Exchange. The results show that CEO ethnicity and operational complexity significantly influence financial reporting timeliness. Financial reporting complexity demonstrates conditional effects depending on leverage levels. Leverage strengthens the relationship between managerial characteristics and reporting discipline, indicating that creditor monitoring plays a disciplinary and signaling role. The study contributes theoretically by integrating executive demographic attributes with governance and signaling mechanisms in explaining reporting timeliness. Practically, the findings provide insights for regulators, investors, and boards regarding executive selection, monitoring mechanisms, and capital structure management in capital-intensive sectors.